China’s Response to the Financial Crisis and the Impacts on the Chinese Economy and Financial Markets: (A Risk Management perspective) - Gao, Shanshan (2012)
The paper involves discovering how the Chinese government response to the recent financial crisis. The goal is to show that China’s particular situation of its financial market and government intervention was the main reason that China’s banking sector not suffered from the global systematic risk. This has been done by examining policies such as risk management policy. Upon examination of these policies, it becomes clear that government intervention done by the government were not perfectly resisting the risks from financial crisis. However, risk tolerance in Chinese banking sector is higher than others, since Chinese government acts behind it. Through the comparing of the policies’ changes before, during, and after the financial crisis, this paper highlights the dominant power of the government in China’s economic and financial market.